PENGARUH SARANA WISATA TERHADAP KEPUTUSAN BERKUNJUNG KE OBJEK WISATA TAMAN REKREASI SARIMANGGIS SOLOK - Sari, Resti Yunita; Silfeni, Silfeni; Abrian, Youmil (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This research strarted from observation of researcher at Sarimanggis SolokRecreational Park, that there are still many visitor complains about tourism facilities that are notimpact well. This study aims to:1) knowing the tourist facilities in the recreational attractionSarimanggis Solok Recreation Park, 2) Knowing the decision to visit the Sarimanggis SolokTourism Recreation Park, and 3) Knowing whether there is influence between tourism facilitieson the decision to visit the tourist attraction Recreation Park Sarimanggis Solok.This type of research is categorized into causal research. Sampling technique in thisresearch is sampling of purposive counted 81 people. Data collection using questionnaires basedon likert scale that has been tested for its validity and reliability. The result of this study are: 1)Tourism facilities are in bad category (65,4%), 2) Visiting decisions are in sufficient category(81,5%), 3) Tourism facilities influence visiting decisions by 9,3% and 90,7% influenced byother factors such as price, location, promotion, people, physical proof and process.Keywords: Tourism Facility, Visiting Decision